PENERAPAN PEMBERIAN BANTUAN HUKUM BAGI MASYARAKAT MISKIN MELALUI POSBAKUM DI PENGADILAN AGAMA KOTA BENGKULU - Fauzan Fauzan (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: The provision of legal aid to date is still not fully felt for the poor, especially the legal and justice aspects. The issuance of Law Number 16 Year 2011 on Legal Aid or so-called UUBH becomes an important breakthrough in constitutional development post-reformasi law. This paper focuses on the provision of legal aid by the Legal Aid Post (Posbakum) in the Religious Court of Bengkulu City. This research is a qualitative research with interview to get data. The results showed that the implementation of legal services through Posbakum in Religious Courts of Bengkulu City has been going well. Although in the implementation of legal services is still constrained by the human resources (HR) in Posbakum, but if dihat from the administrative process and the impact of legal aid services, the overall implementation of legal services through Posbakum in the Court of Religion has been running well according to achievements based on legislation